From value chain to value network: Insights for mobile operators - Peppard, Joe; Rylander, Anna (Elsevier Science B.V., Amsterdam., 2006)
The concept of a value chain has assumed a dominant position in the strategic analysis of industries. However, the value chain is underpinned by a particular value creating logic and its application results in particular strategic postures. Adopting a network perspective provides an alternative perspective that is more suited to New Economy organisations, particularly for those where both the product and supply and demand chain is digitized. This paper introduces the value network concept and illuminates on its value creating logic. It introduces Network Value Analysis (NVA) as a way to analyse competitive ecosystems. To illustrate its application, the provision of mobile services and content is explored to identify potential strategic implications for mobile operators.
Keywords: Value chain; Value network; Strategy; Telecommunications; Mobile operators